A Foundation for Verifying Concurrent Programs (Lecture 1) - Leino, Rustan; Müller, Peter; Smans, Jan (FOSAD 2009, Bertinoro, Italy, 2009)
Today’s lecture More examples Preventing deadlocks Using abstraction Building a program verifier